Empowerment Salt Farmers to Alleviate Poverty - Mohammad Hidayaturrahman; Nisful Laily; Eko Agusrianto (International Conferences SDGs 2030 Challenges and Solutions, 2030)
Government policy in empowering salt farmers faces its own dilemma. On the one hand the government in this case the Ministry of Marine Affairs and Fisheries of the Republic of Indonesia to create a program directed at the empowerment of salt farmers to improve welfare and alleviate the poverty of salt farmers and families, ranging from the Salt People Empowerment Program (PUGAR) given to salt farmers groups, diversification of salt farming methods, with geomembrane technology. But the policy is facing its own problems, when the government in this case the Ministry of Trade of the Republic of Indonesia to open import faucet quite freely to salt entrepreneurs. In addition, another policy that becomes a problem for the empowerment of salt farmers is, the purchase price of salt at the farm level is still not in accordance with the provisions set by the government. Good for first quality salt, second quality, and third quality, remain under government regulation. This makes the salt farmers' income not increase, so the desire to prosper the salt farmers becomes difficult to realize. This research was conducted to find out what kind of policy is implemented by the government in empowering salt farmers, especially in Pinggir Papas village, Kalianget, Sumenep, Madura, East Java. To get the research describing reality, this research method is a single case study with descriptive qualitative approach. Thus, this research is done through direct observation of the object at the time of research conducted by using observations and interviews to various informants directly related to salt farmers in Pinggi Papas, Sumenep, East Java. There is a need for a concerted step taken by the government horizontally between departments/ ministries, and vertically, namely the government at all levels, both central, provincial, district, village, to synchronize the salt farmers empowerment program. That way, the ideals and desires to improve the welfare and eliminate the poverty of salt farmers and families, will be realized.